Peran Pendidikan Agama Islam dalam Membentuk Kedisiplinan di Sekolah Dasar Kecamatan Sumedang Selatan, Kabupaten Sumedang - Aryanto, Noval; Firdaus, Sabiq; Noverayanti, Indrie Fauziyah; Hardiansyah, Ricky; Pratama, Dicky Satria; Supriyadi, Tedi (ALSYS, 2025)
Islamic Religious Education in elementary schools not only serves as the teaching of religious material but also as a means to instill discipline and character in students. This research aims to analyze the role of Islamic Religious Education (PAI) in shaping student discipline at the Elementary School in South Sumedang District, Sumedang Regency. The method used is a qualitative approach with data collection techniques through interviews and observations. The results indicate that Islamic Religious Education plays a significant role in instilling discipline values through the habituation of worship practices, such as congregational prayers, exemplary behavior by teachers, and constructive advice. Collaboration between the school and parents also proves to strengthen the formation of student discipline, creating consistency between learning at school and at home. Other supporting factors include good cooperation between teachers and parents, as well as a supportive school environment. This research concludes that the integration of religious education at school and parental support at home is crucial in shaping students' disciplined character, which in turn can enhance the quality of education at the elementary level. The implications of this study emphasize the importance of character development in discipline through Islamic Religious Education, as well as the collaboration between teachers, schools, and parents to ensure the sustainability of student discipline formation in schools. These findings provide a better understanding of the development of more effective strategies or methods for Islamic Religious Education (PAI) and highlight external collaboration in the sustainable formation of student discipline.